Kolaborasi Implementasi Kebijakan Pengelolaan Sampah Nagari di Kabupaten Pasaman Barat: Melihat Peluang dan Inovasi Kebijakan - Alfian Deby Artha; Heru Nurasa; Candradewini (Research and Development Agency Ministry of Home Affairs, 2023)
The attachment to the 2020-2024 RPJMN states that waste is still a problem in Indonesia. This condition is still spread in almost all districts/cities in Indonesia, including West Pasaman Regency. Factually, in West Pasaman Regency, there are still problems with waste being piled up, burned, and/or dumped into rivers and seas. This problem occurs because West Pasaman Regency has not been supported by the effectiveness of a good waste management system, so collaboration between stakeholders is needed in order to implement waste management policies. This research uses descriptive qualitative method. The purpose of this research is to find out which stakeholders are collaborating in waste management, analyze the collaboration that is built between stakeholders, and optimize opportunities in order to improve waste management performance. In grouping stakeholders who are involved in collaboration, researchers use the power-interest grid mapping method. The results of the study show that the collaborating stakeholders consist of: District Head, DPRD, DLH, Nagari Government, DPMN, community, private sector, and NGOs. Collaboration as a basic strengthening concept of synergy in the implementation of policies that have been built between stakeholders has not been effective. Need to utilize and optimize opportunities for collaboration between and/or with other stakeholders.